PENGARUH RASIO ISOPROPIL ALKOHOL TERHADAP RECOVERY DAN KARAKTERISTIK SERBUK PEKTIN DARI KULIT KAKAO - Venitalitya A. S. Augustia; Dian Ika Nugraha; Sang Kompiang Wirawan (Jurnal Teknik Kimia USU, 2018)
Cocoa is a fruit crop which is able to be planted in tropical climate, e.g. Indonesia. Generally, people only take the flesh of cocoa fruit and the peel is removed so that it will increase the volume of waste. The cocoa peel contains useful compounds for food and pharmaceutical industries, such as pectin. Hence, a research to increase the pectin retrieval quality from cocoa peel is needed in order to utilize the useful cocoa waste. Methods used in this research is solid-liquid extraction with water as solvent in the presence of acid (HCl). The process of making pectin powder is done through several steps here: (1) Raw material preparation, (2) Pectin extraction, and (3) Analysis of pectin powder. The extraction process is done at temperature of 70℃ for 90 minutes with the pH of the solvent is 1.5. The variation is done on the ratio of volume of isopropyl alcohol to the retrieved pectin. The result of the research shows that the recovery of pectin is at its peak at 6.50% with the percentage of water at 5,82%, equivalent weight of 6454,5242, metoxyl percentage of 5,76%, galacturonate percentage of 35,45%, and esterification level of 92,31%. The best quality of pectin, determined by the highest value of characterization, is obtained when the ratio of the filtrate to the volume of isopropyl alcohol is 1:1.